Identification of a Rare EGFR T790I Mutation in Lung Adenocarcinoma Sensitive to Osimertinib - Yu Wang; Songtao Liu; Alei Feng; Huan Luo; Jinwei Hu; Kai Wang; Wei Dong; Wei Dong (Frontiers in Oncology, 2021)
Estimated glomerular filtration rate (EGFR)-sensitive mutations are extremely important for targeted treatment strategies in lung cancer. Osimertinib can effectively inhibit the activity of EGFR-sensitive mutations, including the T790M mutation. However, the efficiency of osimertinib for rare mutation types of T790 is unclear. Here, we report the case of a Chinese patient with lung adenocarcinoma (LADC) harboring a T790I mutation who achieved significant benefits from osimertinib treatment.